2020
DOI: 10.1212/cpj.0000000000000680
|View full text |Cite
|
Sign up to set email alerts
|

Video research visits for atypical parkinsonian syndromes among Fox Trial Finder participants

Abstract: BackgroundUse of video research visits in neurologic conditions is rising, but their utility has not been assessed in atypical parkinsonian syndromes. We sought to evaluate the diagnostic concordance between video-based vs self-reported diagnoses of multiple system atrophy, progressive supranuclear palsy, dementia with Lewy bodies, and corticobasal syndrome. We also assessed patient satisfaction with video-based visits.MethodsWe conducted a study of video-based research visits in individuals with an atypical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
0
20
0
1
Order By: Relevance
“…Participant factors (age, access/familiarity with technology, disease stage, cognitive status) can present additional challenges. In our experience, remote visits can be successfully conducted among older individuals and those with substantial disability [15] and may be even more valuable among this group given their travel-related challenges and higher risk for worse outcomes with COVID-19 [16]. To improve participant comfort and the likelihood of success, adequate preparation is critical.…”
mentioning
confidence: 99%
“…Participant factors (age, access/familiarity with technology, disease stage, cognitive status) can present additional challenges. In our experience, remote visits can be successfully conducted among older individuals and those with substantial disability [15] and may be even more valuable among this group given their travel-related challenges and higher risk for worse outcomes with COVID-19 [16]. To improve participant comfort and the likelihood of success, adequate preparation is critical.…”
mentioning
confidence: 99%
“…Similar outcome assessments are included in subsequent annual visits along with the addition of the clinician and patient global impression of change 29 . After each video visit, participants are surveyed on their experience (technical quality, comfort, and convenience) with the video visits based on surveys developed from previous studies 32,33 . Data from each video visit are entered directly into REDCap.…”
Section: Methodsmentioning
confidence: 99%
“…Vital signs may be useful in some patients, and many have digital thermometers and portable blood pressure cuffs; assessment of orthostatic vital signs is feasible with instruction. 11 Among those without this equipment, the neurologist or onsite helpers can assess respiratory rate, and savvy patients or family members could be instructed to take a radial pulse. The clinician can also demonstrate provocative orthopedic maneuvers (e.g.…”
Section: Essential Components Of the General Examination Vary Based Omentioning
confidence: 99%
“…Reassuringly, assessment of remote encounters across multiple neurological conditions demonstrates that patients and neurologists establish similar comfort as compared to routine in-person visits. 11,28,29 Again, older patients with neurological disease or those with advanced disability may feel less comfortable with the use of technology. While prior studies have demonstrated the feasibility of remote visits among those with advanced neurodegenerative conditions, patients or families with greater baseline comfort with visits may self-select for participation in these studies, limiting generalizability.…”
Section: Limitations Of the Remote Neurological Examinationmentioning
confidence: 99%